Primary frozen section diagnosis by robotic microscopy and virtual slide telepathology: the University Health Network experience. - Evans, A; Chetty, R; Clarke, B; Croul, S; Ghazarian, D; Kiehl, T; Ordonez, B; Ilaalagan, S; Asa, S (2009)
Although telepathology (TP) has not been widely implemented for primary frozen section diagnoses, interest in its use is growing as we move into an age of increasing sub-specialization and centralization of pathology services. University Health Network (UHN) is a 3-site academic institution in downtown Toronto. The pathology department is consolidated at its Toronto General Hospital (TGH) site. The Toronto Western Hospital (TWH), located 1 mile to west of TGH, has no on-site pathologist and generates 5-10 frozen section cases per week. Over 95% of these frozen sections are submitted by neurosurgeons, in most cases to confirm the presence of lesional tissue and establish a tissue diagnosis. In 2004, we implemented a robotic microscopy (RM) TP system to cover these frozen sections. In 2006, we changed to a virtual slide (VS) TP system. Between November 2004 and September 2006, 350 primary frozen section diagnoses were made by RM. An additional 633 have been reported by VS TP since October 2006, giving a total of 983 frozen sections from 790 patients. Eighty-eight percent of these cases have been single specimens with total turnaround times averaging 19.98 and 15.68 minutes per case by RM and VS TP, respectively (P < 0.0001). Pathologists required an average of 9.65 minutes to review a slide by RM. This decreased 4 fold to 2.25 minutes following the change to VS TP (P < 0.00001). Diagnostic accuracy has been 98% with both modalities and our overall deferral rate has been 7.7%. Mid-case technical failure has occurred in 3 cases (0.3%) resulting in a delay where a pathologist went to TWH to report the frozen section. Discrepant cases have typically involved minor interpretive errors related to tumor type. None of our discrepant TP diagnoses have had clinical impact to date. We have found TP to be reliable and accurate for frozen section diagnoses. In addition to its superior speed and image quality, the VS approach readily facilitates consultation with colleagues on difficult cases. As a result, there has been greater overall pathologist satisfaction with VS TP.